Multifunctional Supercapacitors: Rational Design of Nanostructured Electrode Materials toward Multifunctional Supercapacitors (Adv. Funct. Mater. 2/2020). (10th January 2020) - Yan, Jian; Li, Shaohui; Lan, Binbin; Wu, Yucheng; Lee, Pooi See
Abstract : In article number 1902564, Yucheng Wu, Pooi See Lee, and co‐workers discuss the relationship between the capacitive performance and nanostructured materials in achieving high electrochemical performance of active materials for supercapacitors. The enriched functionalities of supercapacitors in a smart way and minimizing the overall integrated size of the functional electronics with improved service life will be key strategies in near future.